Coronary artery stenting in elderly patients: where are we now. (June 2014) - Donahue, Michael; Briguori, Carlo
With the increase of the elderly population, the number of these patients undergoing percutaneous coronary intervention (PCI) has increased considerably. The elderly are, given the presence of comorbidities and frailty, at higher risk of mortality and morbidity following PCI. However, the elderly appear to derive significant benefits in terms of quality of life and might derive greater benefits from revascularization compared with younger patients. PCI is clearly effective in old age, but a careful approach to patient selection is essential to obtain better outcomes. In this qualitative review, we sought to examine the role and the risks of PCI in the older patients and the strategies to lower the adverse events in this particular set of patients.